Liquids till lunch : 12 small habits that will change your life for good - Ghiyam, MaryRuth; Durand, Sarah (HarperOne, an imprint of HarperCollins Publishers, 2021)
"In 2013, MaryRuth was in six figure personal debt, devastated by sudden the loss of her father and brother and struggling in the wake of the Lehman Brothers collapse. A trained nutritional consultant and culinary chef, MaryRuth turned to her passion: helping others lead balanced, healthy lives. She started consulting clients using twelve core principles that could help individuals discover lasting health. These tools worked, her business grew, and this led to the founding of MaryRuth Organics in 2014 with one product. Six years later, MaryRuth Organics has grown into a multi-million dollar business with an incredibly dedicated customer base. MaryRuth embodies the life mission of her brand -- to help others feel and perform their best. Liquids Till Lunch is a road map for guidance and inspiration, outlining rules readers can follow to substantially improve their health, happiness, and mindset. From the importance of portion control to positivity, from fasting to stressing less, each chapter is packed with life-changing anecdotes from her clients, and scientifically backed research. Like B.J. Fogg's TINY HABITS, this book is about the micro changes you can take to change your life in a big way. Using these methods, clients have overcome health and emotional obstacles they once thought were impossible. And they did it by tackling the greatest challenge of all: being kind to themselves."--